Preemptive Activation of the Integrated Stress Response Protects Mice From Diet‐Induced Obesity and Insulin Resistance by Fibroblast Growth Factor 21 Induction. Issue 6 (5th November 2018) - Xu, Xu; Krumm, Christopher; So, Jae‐Seon; Bare, Curtis J.; Holman, Corey; Gromada, Jesper; Cohen, David E.; Lee, Ann‐Hwee
Abstract : Integrated stress response (ISR) is a signaling system in which phosphorylation of eukaryotic translation initiation factor 2α (eIF2α) by stress‐specific kinases and subsequent activation of activation transcription factor (ATF) 4 help restore cellular homeostasis following exposure to environmental stresses. ISR activation has been observed in metabolic diseases, including hepatic steatosis (HS), steatohepatitis (SH), and insulin resistance (IR), but it remains unclear whether ISR contributes to disease pathogenesis or represents an innate defense mechanism against metabolic stresses. Constitutive repressor of eIF2α phosphorylation (CReP) is a critical regulatory subunit of the eIF2α phosphatase complex. Here, we show that CReP ablation causes constitutive eIF2α phosphorylation in the liver, which leads to activation of the ATF4 transcriptional program including increased fibroblast growth factor 21 (FGF21) production. Liver‐specific CReP knockout (CReP LKO ) mice exhibited marked browning of white adipose tissue (WAT) and increased energy expenditure and insulin sensitivity in an FGF21‐dependent manner. Furthermore, CReP LKO mice were protected from high‐fat diet (HFD)‐induced obesity, HS, and IR. Acute CReP ablation in liver of HFD‐induced obese mice also reduced adiposity and improved glucose homeostasis. Conclusion: These data suggest that CReP abundance is a critical determinant for eIF2α phosphorylation and ensuing ISR activation in the liver. Constitutive ISR activation in the liver induces FGF21 and confers protection from HFD‐induced adiposity, IR, and HS in mice. Augmenting hepatic ISR may represent a therapeutic approach to treat metabolic disorders.